2013
DOI: 10.1111/jicd.12055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface roughness and dimorphism on the adhesion of Candida albicans to the surface of resins: scanning electron microscope analyses of mode and number of adhesions

Abstract: Adhesion of yeast-form C. albicans was indifferent to surface roughness. In contrast, mycelial adhesion increased with surface roughness of the resin because mycelia infiltrated the minute protuberances on rough surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 16 publications
1
35
0
3
Order By: Relevance
“…Increased surface roughness can facilitate bacterial accumulation, which then promotes development of denture stomatitis, caries, and periodontal disease 8,9,30) . In addition, it was reported that the morphological transformation between fungal blastospores and hyphae in C. albicans biofilm coincides with an increase in surface roughness of denture acrylic resin 31,32) , a phenomenon attributed to thigmotropism (contact sensing) by C. albicans, in which yeast cells switch to hyphal growth upon contact with a surface 33) . Invasion of hyphae via a few cracks in resin induces hyphal growth and formation of biofilm 34) , thus increasing pathogenicity and virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Increased surface roughness can facilitate bacterial accumulation, which then promotes development of denture stomatitis, caries, and periodontal disease 8,9,30) . In addition, it was reported that the morphological transformation between fungal blastospores and hyphae in C. albicans biofilm coincides with an increase in surface roughness of denture acrylic resin 31,32) , a phenomenon attributed to thigmotropism (contact sensing) by C. albicans, in which yeast cells switch to hyphal growth upon contact with a surface 33) . Invasion of hyphae via a few cracks in resin induces hyphal growth and formation of biofilm 34) , thus increasing pathogenicity and virulence.…”
Section: Discussionmentioning
confidence: 99%
“…As in previous investigations on the adherence and biofilm formation of Candida albicans to denture‐base resins, the arithmetic Ra was chosen to represent the surface roughness in the present study …”
Section: Discussionmentioning
confidence: 99%
“…While some studies have shown that, during initial adherence, C. albicans is retained in greater amounts on rough surfaces in comparison to smooth acrylic surfaces, others have observed no significant influence of surface roughness on the initial attachment of C. albicans . It is important to note, however, that although in these studies the substrates were prepared to produce different surface morphologies, only a few investigated the adherence of C. albicans to denture‐base resins over wider range of roughness . Moreover, to date, only a few studies have reported on the effect of surface roughness on C. albicans biofilm formation (mature biofilm) on denture‐base resins .…”
Section: Introductionmentioning
confidence: 99%
“…Candida species, particularly C. albicans , which are a part of the human oral microbiota, have been reported as the main etiological agents responsible for the development of this inflammatory infection (6). Adherence of C. albicans to the host mucosal tissues (7) and also on the acrylic denture surfaces prepares reservoirs that produce proteolytic enzymes and damage mucosal tissues resulting in denture stomatitis (8). …”
Section: Introductionmentioning
confidence: 99%